Trends in riverine element fluxes: A chronicle of regional socio-economic changes. (15th November 2017) - Kopáček, Jiří; Hejzlar, Josef; Porcal, Petr; Posch, Maximilian
Abstract: We show how concentrations of water solutes in the Vltava River (Czech Republic) and their riverine outputs from the catchment were modified by socio-economic changes, land use, and hydrology between 1960 and 2015. In the early 1960s, HCO3 and Ca were the dominant ions. During 1960–1989 (a period of planned economy with an over-use of synthetic fertilizers, excessive draining of agricultural land and little environmental protection), the riverine concentrations of strong acid anions (SAAs: SO4, NO3, and Cl) increased 2–4-fold and their leaching was accompanied for by a 1.4–1.8-fold increase in concentrations of Ca, Mg, K, and Na. SAAs mostly originated from diffuse agricultural sources (synthetic fertilizers and mineralization of organic matter in freshly drained and deeply tilled agricultural land) and their annual average concentrations (as well as those of Ca, Mg, and K) were positively correlated with discharge. During 1990–2015 (a period of a re-established market economy, reduced fertilization, ceased drainage, partial conversion of arable land to pastures, and increasing environmental protection), concentrations of SO4 and NO3 significantly decreased due to reduced agricultural production and atmospheric pollution, and their positive correlations with discharge disappeared. In contrast, Na and Cl concentrations increased due to more intensive road de-icing, and their concentrations became negatively correlated with discharge. Trends in phosphorus concentrations reflected changes in its input by both diffuse (fertilizers) and point (wastewater) sources and were discharge independent. Graphical abstract: Highlights: We evaluate leaching of S, N, P, Cl and base cations from a large European basin. Riverine element outputs were from 2% (P) to 99% (Cl) of their inputs in 1960–2015. Riverine fluxes of most elements exhibited hystereses compared to their inputs. Socio-economy, land-use and legislation governed sizes of diffuse and point sources. These sizes determined effects of hydrology on riverine element concentrations.